2016
DOI: 10.1186/s12884-016-0950-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal Helicobacter Pylori infection on birth weight in an urban community in Uganda

Abstract: BackgroundHelicobacter pylori, a widespread infection particularly in developing countries has been associated with many adverse effects during pregnancy including hyperemesis gravidarum, neural tube defects in newborns, intrauterine fetal growth restriction and miscarriage. We sought to document the effects of H. pylori infection on birth weight in a low-income setting in Kampala, Uganda.MethodsThis was a prospective cohort study conducted in Kampala between May 2012 and May 2013. The participants were H. pyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
3
13
3
Order By: Relevance
“…6 Likewise, Grooten et al 7 reported marked associations between H. pylori infection and LBW or small for gestational age. This observation was in line with a Ugandan study that recorded a 3.6-fold increased risk of LBW delivery among women infected with H. pylori.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6 Likewise, Grooten et al 7 reported marked associations between H. pylori infection and LBW or small for gestational age. This observation was in line with a Ugandan study that recorded a 3.6-fold increased risk of LBW delivery among women infected with H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmodium falciparum) is a preventable cause of LBW among endemic countries, particularly those in Sub-Saharan Africa. 6,7 In general, data on the association between H. pylori and LBW are scare. Helicobacter pylori) can also lead to LBW.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…36 Di Simone et al 37 also found a higher seroprevalence of In a prospective cohort study conducted in Uganda, H. pylori infection was associated with low birthweight among 221 participants (primigravidae and secundigravidae) (OR: 3.6, 1.1-11.5; P=.031). 38 In another study conducted in the Netherlands, 39 H. pylori positivity was associated with a reduction of total weight gain in women with daily vomiting (adjusted difference, −2.1 kg; −2.7 to −1.5); infants born to women with H. pylori and daily vomiting had slightly reduced birthweight (adjusted difference −60g; −109 to −12) and an increased risk of being small for gestational age (OR: 1.49, 1.04-2.14). H. pylori and daily vomiting did not significantly affect the prematurity rate.…”
Section: Pregnancymentioning
confidence: 99%